Mexican ethnic economy: social mobility factor and economic improvement for their employees? - Peraza-Noriega, Brianda Elena (Universidad Autónoma de Tamaulipas, 2015)
California has developed commercial areas that emulate the atmosphere of popular markets of large Mexican cities. These commercial areas have flourished due to the presence of Mexican immigrants, who found in the ethnic economy a space that serves as both, a place for working and a medium to spread mainly their gastronomic and musical culture. The aim of this study was to analyze the economic and cultural processes associated with ethnic businesses located in Los Angeles area, particularly Huntington Park and Lynwood, California. The research project has a twofold purpose. It firstly attempts to find out if the ethnic economy in the region is a platform for upward social mobility for Mexican migrants who work for their fellow citizens. Secondly, it attempts to assess the role of these businesses in processes of cultural dissemination and preservation. The main methodological tool was the ethnographic survey, administered to 32 Mexican immigrants working in the ethnic economy and to an equal number of Mexican migrant workers who worked in other businesses located in the same cities. Sixty one questionnaires were also applied to Mexican immigrant entrepreneurs. The results confirmed that these ethnic businesses generate attractive economic returns for business owners but not for the workers, who earn low wages. Although this situation prevents upward mobility for workers, there are exceptional cases of immigrants who started as employees but managed to become entrepreneurs. We conclude that although the Mexican ethnic economy in Los Angeles reproduces a lack of social mobility, it is still an area of opportunity for migrants who find their first job there. Additionally, this market recreates and disseminates the Spanish language and the material culture of migrants. Archive XML (SciELO)